Broadband angular spectrum differentiation using dielectric metasurfaces - Deng, Ming; Cotrufo, Michele; Wang, Jian; Dong, Jianji; Ruan, Zhichao; Alù, Andrea; Chen, Lin (Nature communications, 2024)
Signal processing is of critical importance for various science and technology fields. Analog optical processing can provide an effective solution to perform large-scale and real-time data processing, superior to its digital counterparts, which have the disadvantages of low operation speed and large energy consumption. As an important branch of modern optics, Fourier optics exhibits great potential for analog optical image processing, for instance for edge detection. While these operations have been commonly explored to manipulate the spatial content of an image, mathematical operations that act directly over the angular spectrum of an image have not been pursued. Here, we demonstrate manipulation of the angular spectrum of an image, and in particular its differentiation, using dielectric metasurfaces operating across the whole visible spectrum. We experimentally show that this technique can be used to enhance desired portions of the angular spectrum of an image. Our approach can be extended to develop more general angular spectrum analog meta-processors, and may open opportunities for optical analog data processing and biological imaging. Metasurfaces processing incoming images have been proposed in the context of real space operations. Here, the authors demonstrate mathematical operations, such as differentiation, on the angular spectrum of an image using metasurfaces, which can be used to enhance spectral features of an image.